Data Spacing of Interferogram for Static Modulation in Fourier Transform Infrared Spectrometer - Yong Cho, Ju; Kyu Park, Hyun; Seok Ji, Min; Kweon Jang, Won (Asian Journal of Chemistry, 2015)
The maximum data spacing of the interferogram for exact spectral information of unknown species was discussed in two dimensional Fourier transform technology for static modulation. We investigated the optimized sampling frequency enough to get the moderate interferogram without superfluous data, based on Nyquist theorem. The Fourier transform infrared spectrometer with a stationary interferometer composed of optical elements creating retardation must use the restrained number of data. The minimum number of data for the static modulated Fourier transform spectrometer was discussed to replace the dynamic modulation in the conventional Fourier transform spectrometers.